2013
DOI: 10.1093/cvr/cvt009
|View full text |Cite
|
Sign up to set email alerts
|

Redox-dependent increases in glutathione reductase and exercise preconditioning: role of NADPH oxidase and mitochondria

Abstract: Adaptive cardioprotective signalling is triggered by reactive oxygen species from NADPH oxidase, and leads to improved glutathione replenishment through redox-dependent modifications in GR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 77 publications
4
64
0
Order By: Relevance
“…Notably, exercisebased cardiac rehabilitation has been shown to improve exercise tolerance and reduce mortality in CAD patients [11][12][13]. Meanwhile, it has been documented in animal models produce preconditioning stimuli [14][15][16][17][18][19], thus making the heart more resistant to cardiac injury following myocardial ischemia-reperfusion (I/R) [20][21][22][23]. Also, it has previously been demonstrated that long-term exercise training (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, exercisebased cardiac rehabilitation has been shown to improve exercise tolerance and reduce mortality in CAD patients [11][12][13]. Meanwhile, it has been documented in animal models produce preconditioning stimuli [14][15][16][17][18][19], thus making the heart more resistant to cardiac injury following myocardial ischemia-reperfusion (I/R) [20][21][22][23]. Also, it has previously been demonstrated that long-term exercise training (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, an increase in the activity of the enzyme glutathione reductase was observed after exercise (22). However, some studies have observed an increase in the catalase activity after exercise (23,24) some observed no change (25,26), and some found even lower (27) activity that could have implications on the role of the increase in glutathione as coenzyme glutathione oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is known to protect against arrhythmia (27,30,36,60), as well as other postischemic damage, such as myocardial stunning (11,46,66) and infarction (14,29,58,59). Despite the clear beneficial effect, the underlying cellular mechanisms are not completely understood.…”
Section: New and Noteworthymentioning
confidence: 99%
“…Several factors, including various genetic abnormalities, channelopathies, compromised autonomic function, left ventricular hypertrophy, and acute coronary syndromes, are known to influence the susceptibility to arrhythmia (26, 53, 68). During acute coronary syndromes, the reperfusion of previously ischemic tissue leads to a burst in reactive oxygen species (ROS), a significant contributor to electromechanical dysfunction (3,10,48,75).Exercise is known to protect against arrhythmia (27,30,36,60), as well as other postischemic damage, such as myocardial stunning (11,46,66) and infarction (14,29,58,59). Despite the clear beneficial effect, the underlying cellular mechanisms are not completely understood.…”
mentioning
confidence: 99%